A comparative study of clinical profile and symptom control in overweight and normal weight school‐age children with mild persistent asthma. Issue 1 (21st December 2020) - Manivannan, Sharmila; Chandrasekaran, Venkatesh; Subramanian, Nandheeswari
Abstract: Objectives: To find out the proportion of children with poor symptom control in overweight/obese and normal weight children with mild persistent asthma and to know the sociodemographic and clinical correlates of poor symptom control in them. Materials and Methods: Children aged 6 to 12 years with mild persistent asthma with BMI Z score for age and sex more than +1 Z score on WHO BMI Z score chart for age and sex formed the cases. Age‐ and sex‐matched asthmatics with BMI Z score for age and sex between −2 Z and +1 Z score formed the controls. FEV1, FEV1/FVC were measured in both groups using Care Fusion Jaeger spirometer. Symptom control was assessed by ACT score. Statistical analysis was done using SPSS version 19 and Vassarstats. Results: The proportion of children with poor control was 19.1% in the overweight/obese group and 23.4% in the normal weight group. There was no significant correlation between BMI and symptom control as assessed by the ACT score. Overweight/obese children with good control showed a slightly lower FEV1/FVC ratio and higher median eosinophil count compared to children with normal weight. Gastroesophageal reflux and allergic rhinitis were more commonly seen in overweight/obese children. In the poor control group, FEV1, FEV1/FVC, and median eosinophil counts were not significantly different between overweight/obese and normal weight group but were less when compared to good control group. Conclusion: The proportion of poor symptom control was not high in overweight/obese asthmatic children compared to normal weight asthmatic children. No significant risk factors for poor symptom control could be identified in our study for either of the groups.